Battle for Britain: Analyzing Events as Drivers of Political Tribalism in Twitter Discussions of Brexit. Issue 2 (12th August 2020) - North, Samantha; Piwek, Lukasz; Joinson, Adam
Abstract : In the aftermath of the 2016 referendum on European Union (EU) membership, Britain was divided into identity groups (or tribes) of Leavers and Remainers. In this study, we investigate how Brexit tribalism—in the form of outgroup derogation—has unfolded over time on Twitter. We analyze data from 32 months of discussions ( n  = 9, 027, 822), using identity‐based keywords as proxies for tribalism. First, we characterize the nature of the discussion by comparing language use patterns between tweets containing Brexiteer/Remainer and Brextremist/Remoaner keywords. We find that Brextremist/Remoaner are more commonly used in a derogatory way. We also find that all four group identity keywords are used more frequently over time, suggesting an increase in tribal interactions. Finally, we find evidence of a relationship between real‐life Brexit events and spikes in tribal responses online. These findings provide compelling insights into the extent of tribal political behavior on social media. They are significant for furthering our understanding of tribalism as a central feature of information warfare campaigns that aim to divide societies. Abstract : 2016年就欧盟成员国身份进行公投后, 英国被划分为"脱欧支持者"和"脱欧反对者"两个认同团体(或部落)。本研究中, 我们调查了英国脱欧部落主义—以外群贬义的形式—如何在推特上随时间推移而展开。我们分析为期32个月的辩论数据(n = 9, 027, 822), 使用基于认同的关键词作为部落主义的指标。首先, 我们通过比较包含关键词"脱欧支持者/脱欧反对者"(Brexiteer/Remainer) 与"脱欧极端主义者/不脱欧抱怨者"(Brextremist/Remoaner)的推文的语言使用模式, 对该辩论的性质进行了描述。我们发现, 脱欧极端主义者/不脱欧抱怨者这组关键词更常以贬义的方式进行使用。我们还发现, 这四个团体认同关键词随时间推移使用次数更频繁, 暗示部落相互影响情况的增加。最后, 我们发现现实生活中的脱欧事件与网上部落响应的激增之间存在联系。这些研究发现就社交媒体上部落政治行为的范围提供了具有说服力的见解。研究发现的重要性在于加深我们对部落主义的理解, 这种部落主义是以划分社会为目的的信息战活动的一个中心特征。 Abstract : A raíz del referéndum de 2016 sobre la membresía en la Unión Europea (UE), Gran Bretaña se dividió en grupos de identidad (o tribus) de Leavers y Remainers. En este estudio, investigamos cómo el tribalismo del Brexit, en forma de derogación fuera del grupo, se ha desarrollado con el tiempo en Twitter. Analizamos datos de 32 meses de debates (n = 9.027.822), utilizando palabras clave basadas en la identidad como representantes del tribalismo. Primero, caracterizamos la naturaleza de la discusión comparando los patrones de uso del lenguaje entre tweets que contienen palabras clave Brexiteer/Remainer y Brextremist/Remoaner. Encontramos que Brextremist/Remoaner se usan más comúnmente de una manera despectiva. También encontramos que las cuatro palabras clave de identidad de grupo se usan con más frecuencia a lo largo del tiempo, lo que sugiere un aumento en las interacciones tribales. Finalmente, encontramos evidencia de una relación entre los eventos Brexit de la vida real y los picos en las respuestas tribales en línea. Estos hallazgos proporcionan información convincente sobre el alcance del comportamiento político tribal en las redes sociales. Son importantes para ampliar nuestra comprensión del tribalismo como una característica central de las campañas de guerra de información que tienen como objetivo dividir a las sociedades.